The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/cr.2015.12
|View full text |Cite
|
Sign up to set email alerts
|

FXYD2, a γ subunit of Na+,K+-ATPase, maintains persistent mechanical allodynia induced by inflammation

Abstract: Na+ ,K + -ATPase (NKA) is required to generate the resting membrane potential in neurons. Nociceptive afferent neurons express not only the α and β subunits of NKA but also the γ subunit FXYD2. However, the neural function of FXYD2 is unknown. The present study shows that FXYD2 in nociceptive neurons is necessary for maintaining the mechanical allodynia induced by peripheral inflammation. FXYD2 interacted with α1NKA and negatively regulated the NKA activity, depolarizing the membrane potential of nociceptive n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 44 publications
(59 reference statements)
2
42
0
Order By: Relevance
“…Gene expression profiles of DRG tissue have been also analyzed by microarray and RNA-sequencing (RNA-seq) techniques [17,18]. Although these methods have helped to identify the expression of neuromodulators such as natriuretic peptide B (NPB) [19] and regulators of Na + , K + -ATPase (NKA), including the γ-subunit of NKA (FXYD domain-containing ion transport regulator 2, Fxyd2) [20][21][22], they cannot provide a global view of the transcriptional profiles of individual neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Gene expression profiles of DRG tissue have been also analyzed by microarray and RNA-sequencing (RNA-seq) techniques [17,18]. Although these methods have helped to identify the expression of neuromodulators such as natriuretic peptide B (NPB) [19] and regulators of Na + , K + -ATPase (NKA), including the γ-subunit of NKA (FXYD domain-containing ion transport regulator 2, Fxyd2) [20][21][22], they cannot provide a global view of the transcriptional profiles of individual neurons.…”
Section: Introductionmentioning
confidence: 99%
“…This would also validate that the antibody beads were binding intact exosomes. The transmembrane protein ion channel regulator FXYD2 isoforms γa and γb is reported to be an islet β cell-specific surface marker compared with exocrine pancreas (19)(20)(21)(22). Therefore, we assessed for FXYD2 surface coexpression Figure 4B).…”
Section: Transplanted Human Islets Release Donor Mhc-specific Exosomementioning
confidence: 99%
“…These findings provide FSTL1 as a first endogenous NKA agonist that regulates synaptic transmission. Furthermore, they also revealed that the FXYD2/α1NKA interaction increased after inflammation, resulting in reduction of NKA activity, depolarization of neuron membrane and facilitation of excitatory afferent neurotransmission (Wang et al, 2015), revealing a fundamental mechanism underlying the persistent inflammatory pain.…”
Section: Exploration Of Novel Mechanisms Involved In Pain Regulationmentioning
confidence: 99%